Today's Organizational Strategy: Integrating Innovation, Leadership, and Work Climate to Improve Job Performance - Deni Surapto (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: In today’s organizational environment, employee performance is critically influenced by innovation ambidexterity, agile leadership, and organizational climate. Objective: This study aims to analyze the influence of innovation ambidexterity, agile leadership, and organizational climate on job performance among distance learning lecturers in Indonesia. Methods: A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. Data were collected from 363 lecturers via a structured 5-point Likert-scale questionnaire. Reliability and validity were assessed using Cronbach’s alpha, composite reliability, AVE, outer loadings, HTMT, and R², while common method bias was controlled using full collinearity variance inflation factors (FCVIFs). Hypothesis testing was conducted using path coefficients and t-statistics (α = 0.05). Results: Innovation ambidexterity had the strongest significant impact on job performance (β = 0.5718; t = 10.1420), followed by organizational climate (β = 0.1476; t = 3.8438) and agile leadership (β = 0.1196; t = 3.0233). The model explained 47.42% of the variance in job performance (R² = 0.4742; adjusted R² = 0.4698) and showed no evidence of common method bias (FCVIF = 1.902). Conclusion: Effectively integrating innovation ambidexterity, agile leadership, and a supportive organizational climate enhances employee performance. Organizations are recommended to institutionalize balanced innovation strategies, foster adaptive leadership, and cultivate a positive work environment to optimize productivity.